Boost Tendon/Ligament Repair With Biomimetic and Smart Cellular Constructs - Zhao, Jianping; Wang, Xiang; Han, Jinyu; Yu, Yin; Chen, Fei; Yao, Jun (Frontiers in Bioengineering and Biotechnology, 2021)
Tendon and ligament are soft connective tissues that play essential roles in transmitting forces from muscle to bone or bone to bone. Despite significant progress made in the field of ligament and tendon regeneration over the past decades, many strategies struggle to recapitulate basic structure-function criteria of native ligament/tendon. The goal here is to provide a fundamental understanding of the structure and composition of ligament/tendon and highlight few key challenges in functional regeneration of these connective tissues. The remainder of the review will examine several biomaterials strategies including biomimetic scaffold with non-linear mechanical behavior, hydrogel patch with anisotropic adhesion and gene-activated scaffold for interactive healing of tendon/ligament. Finally, emerging technologies and research avenues are suggested that have the potential to enhance treatment outcomes of tendon/ligament injuries.